A Literature Review of Tax Avoidance - Ade Imam Muslim; Doddy Setiawan (Assets: Jurnal Akuntansi dan Pendidikan, 2020)
ABSTRACTThis study aims to provide an overview of the development of tax avoidance research. Data is taken from publishers Emerald, Ebsco, Wiley, Springer, and Proquest database. Samples from 2005 to 2019 and 77 articles were obtained covering tax avoidance. The method of analysis is through article classification by topic, source of scientific discipline, journal name, measurement of tax avoidance, distribution of article years, and references. In sum, the results of the study found that tax avoidance research has increased from year to year and still an interesting topic to study.ABSTRAKPenelitian ini bertujuan memberikan gambaran tentang pengembangan penelitian penghindaran pajak. Data diambil dari penerbit Emerald, Ebsco, Wiley, Springer, dan Proquest. Sampel diambil dari tahun 2005 sampai dengan tahun 2019 sebanyak 77 artikel penghindaran pajak. Metode analisis melalui pengklasifikasian artikel berdasarkan topik, sumber disiplin ilmu, nama jurnal, pengukuran penghindaran pajak, distribusi tahun artikel dan referensi. Secara umum hasil penelitian menemukan bahwa penelitian penghindaran pajak telah meningkat dari tahun ke tahun dan menjadi topik penelitian yang masih menarik untuk diteliti.